The monoicous secondarily aquatic liverwort Ricciocarpos natans as a model within the radiation of derived Marchantiopsida - Singh, Shilpi; Bowman, John L. (Frontiers in Plant Science, 2023)
Liverworts represent one of six embryophyte lineages that have a Devonian, or earlier, origin, and are, at present, represented by only Marchantia polymorpha as an established model. Ricciocarpos natans is a secondarily monoicous aquatic liverwort with a worldwide distribution, being found on all continents except Antarctica. Ricciocarpos, a monotypic genus, forms a sister relationship with Riccia, the largest genus of the Marchantiopsida (~250 species), diverging from their common ancestor in the mid-Cretaceous. R. natans is typically found on small stagnant ponds and billabongs (seasonal pools), where it assumes a typical ‘aquatic’ form with long scale keels for stabilization on the water surface. But, as water bodies dry, plants may become stranded and subsequently shift their development to assume a ‘terrestrial’ form with rhizoids anchoring the plants to the substrate. We developed R. natans as a model to address a specific biological question — what are the genomic consequences when monoicy evolves from ancestral dioicy where sex is chromosomally determined? However, R. natans possesses other attributes that makes it a model to investigate a variety of biological processes. For example, it provides a foundation to explore the evolution of sexual systems within Riccia, where it appears monoicy may have evolved many times independently. Furthermore, the worldwide distribution of R. natans postdates plate tectonic driven continent separation, and thus, provides an intriguing model for population genomics. Finally, the transition from an aquatic growth form to a terrestrial growth form is mediated by the phytohormone abscisic acid, and represents convergent evolution with a number of other aquatic embryophytes, a concept we explore further here.